Beta-Lactams Therapeutic Monitoring in Septic Children–What Target Are We Aiming for? A Scoping Review - Morales Junior, Ronaldo; Pereira, Gabriela Otofuji; Tiguman, Gustavo Magno Baldin; Juodinis, Vanessa D'Amaro; Telles, João Paulo; de Souza, Daniela Carla; Santos, Silvia Regina Cavani Jorge (Frontiers in Pediatrics, 2022)
The antimicrobial therapy of sepsis and septic shock should be individualized based on pharmacokinetic/pharmacodynamic (PK/PD) parameters to deliver effective and timely treatment of life-threatening infections. We conducted a literature scoping review to identify therapeutic targets of beta-lactam antibiotics in septic pediatric patients and the strategies that have been applied to overcome sepsis-related altered pharmacokinetics and increase target attainment against susceptible pathogens. A systematic search was conducted in the MEDLINE, EMBASE and Web of Science databases to select studies conducted since 2010 with therapeutic monitoring data of beta-lactams in septic children. Last searches were performed on 02 September 2021. Two independent authors selected the studies and extracted the data. A narrative and qualitative approach was used to summarize the findings. Out of the 118 identified articles, 21 met the eligibility criteria. Population pharmacokinetic modeling was performed in 12 studies, while nine studies reported data from bedside monitoring of beta-lactams. Most studies were conducted in the United States of America (n = 9) and France (n = 5) and reported PK/PD data of amoxicillin, ampicillin, azlocillin, aztreonam, cefazolin, cefepime, cefotaxime, ceftaroline, ceftazidime, doripenem, meropenem and piperacillin/tazobactam. Therapeutic targets ranged from to 40% fT> MIC to 100% fT> 6 × MIC. Prolonging the infusion time and frequency were most described strategies to increase target attainment. Monitoring beta-lactam serum concentrations in clinical practice may potentially maximize therapeutic target attainment. Further studies are required to define the therapeutic target associated with the best clinical outcomes.